An epidemiological needs assessment of carotid endarterectomy in an English health region. Is the need being met?. Issue 7156 (15th August 1998) - Ferris, G; Roderick, P; Smithies, A; George, S; Gabbay, J; Couper, N; Chant, A
Abstract: Objective: To compare the level of provision of carotid endarterectomy (an intervention of proved efficacy for prevention of stroke in patients with symptomatic high grade carotid artery stenosis) with estimates of need. Design: Comparison of regional, district, and age-sex specific operation rates derived from hospital episode statistics with estimates of need based on demographic and epidemiological data; interviews with regional vascular surgeons and a joint provider-purchaser workshop to discuss implications. Setting: Former Wessex Regional Health Authority, 1991-2 to 1995-6. Subjects: All residents covered by Wessex region treated for carotid artery reconstruction. Main outcome measures: Regional, district, and age-sex operation rates as three year average 1993-6 (use) compared with respective estimates of need for carotid endarterectomy among those who presented with symptomatic carotid disease—transient ischaemic attack or minor stroke. Results: The operation rate more than doubled between 1991-2 and 1995-6, from 35 to 89 per million population, compared with an estimated level of need in the region's general population of 153 per million population (transient ischaemic attack 77, minor stroke 76). The ratio of use to need was 0.47 (95% confidence interval 0.4 to 0.54); district ratios were 0.28 (0.19-0.38) to 0.81 (0.62 to 1.06). The annual use:need ratio rose over the three years 1993-6 from 0.38 to 0.59. Use:need ratios were lower in elderly and female patients. Providers were keen to develop guidelines for referral and to increase access to diagnostic facilities; purchasers were more reluctant, given the limited impact of this intervention on the incidence of stroke and the relatively high cost of the operation. Conclusion: Although treatment rates increased in Wessex there is still unmet need. Further research is needed to determine the referral pathways of patients with symptomatic carotid disease for diagnosis and operation and to evaluate strategies to improve access to diagnostic facilities.